Penyuluhan Bahaya Malware Dan Spiware Dalam Penggunaan Internet Bagi Sekolah - Victor Victor; Hamjah Arrahman; Vera Wijaya; Tony honkly; Rozi Rozi; Niki Niki; Fadya Fadya (Asosiasi Periset Bahasa Sastra Indonesia, 2023)
In accordance with the title of this community service program